Impact of I/O Coordination on a NFS-Based Parallel File System with Dynamic Reconfiguration - Kassick, Rodrigo Virote; Boito, Francieli Zanon; Navaux, Philippe O. A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2010: Anais do XXII International Symposium on Computer Architecture and High Performance Computing, 2010)
The large gap between processing and I/O speed makes the storage infrastructure of a cluster a great bottleneck for UPC applications. Parallel File Systems propose a solution to this issue by distributing data onto several servers, dividing the load of I/O operations and increasing the available bandwidth. However, most parallel file systems use a fixed number of I/O servers defined during initialization and do not support addition of new resources as applications' demands grow. With the execution of different applications at the same time, the concurrent access to these resources can impact the performance and aggravate the existing bottleneck. The dNFSp File System proposes a reconfiguration mechanism that aims to include new I/O resources as application's demands grow. These resources are standard cluster nodes and are dedicated to a single application. This paper presents a study of the I/O performance of this reconfiguration mechanism under two circumstances: the use of several independent processes on a multi-core system or of a single centralized I/O process that coordinates the requests from all instances on a node. We show that the use of coordination can improve performance of applications with regular intervals between I/O phases. For applications with no such intervals, on the other hand, uncoordinated I/O presents better performance.